PENINGKATAN KOMPETENSI DIGITAL SISWA SMKN 1 PANGKEP MELALUI PELATIHAN KODING PYTHON TERSTRUKTUR - Figur Muhammad; Kholik Prasojo; Umi Purnama; Massikki (Journal of Engineering Service and Innovation, 2026)
The development of digital technology requires vocational high school (SMK) students to possess programming competencies as preparation for the digital era. However, many students still experience difficulties in understanding basic programming concepts systematically. This community service activity aimed to improve the digital competence of students at SMKN 1 Pangkep through structured Python coding training. The training was conducted using hands-on learning and project-based learning approaches with materials covering algorithm logic, variables, operators, branching, looping, functions, and simple Python-based application development. The results showed that students were able to understand basic Python programming concepts and successfully develop simple CLI- and GUI-based applications. In addition to improving technical skills, the training also enhanced students’ problem-solving abilities, logical thinking, and learning motivation in digital technology. Therefore, Python coding training can be an effective effort to improve the digital competence of vocational high school students in the era of technological advancement.